Symptom Burden Predicts Nursing Home Admissions Among Older Adults - Sheppard, Kendra D. (2012)
CONTEXT: Symptom burden has been associated with functional decline in community-dwelling older adults and may be responsive to interventions. Known predictors of nursing home (NH) admission are often nonmodifiable. OBJECTIVES: To determine if symptom burden independently predicted NH admission among community-dwelling older adults over an 8½ year follow-up period. METHODS: A random sample of community-dwelling Medicare beneficiaries in Alabama, stratified by race, gender, and rural/urban residence, had baseline in-home assessments of sociodemographic measurements, Charlson comorbidity count, and symptoms. Symptom burden was derived from a count of 10 patient-reported symptoms. Nursing home admissions were determined from telephone interviews conducted every six months over the 8½ years of the study. Cox proportional hazard modeling was used to examine the significance of symptom burden as a predictor for NH admission after adjusting for other variables. RESULTS: The mean±SD age of the sample (N=999) was 75.3±6.7 years, and the sample was 51% rural, 50% African American, and 50% male. Thirty-eight percent (n=380) had symptom burden scores ≥ 2. Seventy-five participants (7.5%) had confirmed dates for NH admission during the 8½ years of follow-up. Using Cox proportional hazard modeling, symptom burden remained an independent predictor of time to NH placement (HR=1.11, P=0.02), even after adjustment for comorbidity count, race, sex and age. CONCLUSION: Symptom burden is an independent risk factor for NH admission. Aggressive management of symptoms in older adults may reduce or delay NH admission.